Frontiers of the Roman Empire : Ffiniau'r Ymerodraeth Rufeinig - Breeze, David J. (Archaeopress Archaeology, 2022)
The remains of the Roman frontiers in Wales are unique in the Roman Empire. More than 60 stone and timber fortresses, forts and fortlets, some of which seem to have been occupied for only a few years, while others remained in use for far longer, tell the story of the long and brutal war against the Celtic tribes.